Seiji Shirane. 2022. Imperial Gateway: Colonial Taiwan and Japan’s Expansion in South China and Southeast Asia, 1895-1945. Ithaca: Cornell University Press. xvi + 266 pp. ISBN 9781501765575 - Medina Galván, Ricardo Misael (Estudios de Asia y África, 2024)
Seiji Shirane. 2022. Imperial Gateway: Colonial Taiwan and Japan’s Expansion in South China and Southeast Asia, 1895-1945. Ithaca: Cornell University Press. xvi + 266 pp. ISBN 9781501765575